Pengaruh Dari Perkembangan Teknologi, Kompetensi dan Keterampilan Terhadap Kinerja Karyawan Di PT BPR Ceper Di Klaten - Bala, Rima Parawati; Wijayanti, Handayani Tri (ITB AAS Indonesia Surakarta, 2024)
The purpose of this research is to analyze the influence of technological development in employee performance at PT BPR Ceper in Klaten. Analyzing the influence of compensation in employee performance at PT BPR Ceper in Klaten. Analyzing the influence of skills in employee performance at PT BPR Ceper in Klaten. The population of this research is employees of PT BPR Ceper Klaten while the sample was 35 respondents using random sampling technique. Meanwhile, multiple linear regression analysis tools, t test, F test and coefficient of determination. Based on the results, it is known that technological developments, compensation and skills effect on employee performance are significant. Thus it can be stated that the first, second and third hypotheses have been proven correct.